The Effect Integrity and Objectivity Auditor Intern to Effectivity Audit Intern with democratic Leadership Style as Variable Moderated on the Inspectorate districts X - Dewa Putu Bayu Permadi; A.A.G.P Widanaputra (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
The purpose of this study was to determine the effect of integrity and objectivity on the effectiveness of internal audit with democratic leadership style as a moderating variable at the X Regency Inspectorate. This research was conducted at the Office of the Inspectorate of X Regency. The number of samples taken as many as 32 auditors, with saturated sampling method. Data was collected through a survey method with data collection techniques using a questionnaire. The analysis technique used is Moderated Regression Analysis.